Spatial targeting of adaptation efforts in the livestock sector - Kimani, Lucy; Hoek, Rein van der; Notenbaert, An Maria Omer (International Center for Tropical Agriculture, 2023)
Climate change has emerged as a significant threat to livestock and the ecosystem goods and services on which they depend. With projections of rising temperatures and CO2 levels, changing rainfall patterns, and increased climate variability and occurrence of extreme events, the direct impacts of climate change on livestock can be seen through behavioural and metabolic changes, including reduced feed intake, increased energy requirement, and decreased conception rates. Additionally, indirect impacts are felt through various channels, including a mismatch between increasing water demand and decreasing water supply, increased pest and disease pressure, biodiversity losses, changes in quantity and quality of feed resources, and changes in overall system productivity and livelihood patterns.